Instruments used in vocational-professional guidance: a topic review - Castaño Acosta, Steeventh; Tobón Vásquez, Gloria del Carmen; Delgado Reyes, Andrés Camilo; Aguirre Aldana, Lorena (Pensando Psicología, 2023)
Vocational guidance can be understood as a process that helps the choice of a profession and the preparation for it, the access to its exercise, the evolution and subsequent progress. The objective of this topic review is to investigate which are the most used instruments at the national and international level when carrying out a vocational guidance process between 2015 and 2020 in secondary education students. A search for articles derived from research was carried out in databases such as Ebscohost, Science Direct, Scopus, Lilacs, Scielo and Redalyc. In the initial inquiry, 1298 articles were registered and based on the exclusion criteria, a total of 23 publications were selected. The analysis carried out leads to identify the instruments used in the last five years, where the SDS is the instrument with the most frequency of use, this is due to the universality in its factorial structure. Knowing the instruments used nationally and internationally will allow the implementation of tools that facilitate more accurate vocational-professional guidance processes and in accordance with cultural needs, currently in Colombia there is a deficit of standardized and valid instruments for vocational guidance processes.